Penggunaan Hidrogen Peroksida pada Kolam Lumpur Aktif Upaya Menghilangkan Filamentous dan Meningkatkan Nilai Index Pengendapan Bio Sludge di PT. X Industri Kertas Jawa Timur - Dewi Intan Elok Mayangsari; Rizka Novembrianto (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
The paper industry is one of the industries that can cause river pollution. The processing industry produced from this forest is a contributor to liquid waste which can harm the environment and the living things that live in it. So that an integrated treatment is needed to reduce the hazardous content of the waste that is disposed of. Bacteria is one way that can be used for non-food or food. Filamentous bacteria are the abnormal growth filaments of certain bacteria, one example of which is Escherichia coli. In this study, the quantitative research method was used. The chemicals used are by adding a 0.5% Hydrogen Peroxide solution at a dose of 4 ppm, and using 5 days. Also, the parameters tested in the aeration tank were DO, pH, MLSS, SVI, microscopic filamentous conditions and in the effluent bath, namely DO, pH, TSS, COD, turbidity. The results in the aeration tank with the pH parameter have an average value of 8.018, DO has an average value of 6.09, MLSS with an average of 3770, and SVI of 122. The results in the effluent bath with a pH parameter have an average of 7, 84. DO has an average of 4.13, turbidity has a value of 21.2-60.3 on the fifth day, COD value has an average of 123, and TSS value has an average value of 74.5.